The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.ejvs.2007.08.012
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Multicentre Clinical Trial Comparing the Efficacy of Calcium Dobesilate with Placebo in the Treatment of Chronic Venous Disease

Abstract: Treatment with calcium dobesilate was not found to be superior to placebo on the QoL of CVD patients. The sustained effect of calcium dobesilate observed after treatment should be confirmed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 18 publications
1
30
0
7
Order By: Relevance
“…Perseverance of the drug is unlikely because elimination of calcium dobesilate after oral administration is 50% at 24 h (Tejerina and Ruiz 1998). Interestingly, in a study of chronic venous disease in humans it was noted that there was a persistent positive effect of dobesilate on quality of life compared to placebo (Martinez-Zapata et al 2008), suggesting a sustained therapeutic action.…”
Section: Discussionmentioning
confidence: 99%
“…Perseverance of the drug is unlikely because elimination of calcium dobesilate after oral administration is 50% at 24 h (Tejerina and Ruiz 1998). Interestingly, in a study of chronic venous disease in humans it was noted that there was a persistent positive effect of dobesilate on quality of life compared to placebo (Martinez-Zapata et al 2008), suggesting a sustained therapeutic action.…”
Section: Discussionmentioning
confidence: 99%
“…This difference was significant at 12 months but not at three months (primary outcome), statistically. 31 This may indicate that single therapy with calcium dobesilate should be supported with others to achieve more improvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis in 2008 involving 509 patients failed to show any edema, symptoms, and quality-of-life in patients consuming calcium dobesilate in comparison with placebo[33] (evidence Level A). A trial demonstrated the increased efficacy of dobesilate with a combination with oxerutins[34] (evidence Level C).…”
Section: Phlebotonics/flavonoidsmentioning
confidence: 99%